2011
DOI: 10.4049/jimmunol.1001783
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype, Function, and Gene Expression Profiles of Programmed Death-1hi CD8 T Cells in Healthy Human Adults

Abstract: T cell dysfunction is an important feature of many chronic viral infections. In particular, it was shown that programmed death-1 (PD-1) regulates T cell dysfunction during chronic lymphocytic choriomeningitis virus infection in mice, and PD-1hi cells exhibit an intense exhausted gene signature. These findings were extended to human chronic infections such as HIV, hepatitis C virus, and hepatitis B virus. However, it is not known if PD-1hi cells of healthy humans have the traits of exhausted cells. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
185
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(209 citation statements)
references
References 64 publications
20
185
0
4
Order By: Relevance
“…17 It should be noted that our gene expression profiling was performed after a period of expansion of isolated TIL with IL-2 in order to generate enough cells for analysis. This may have reversed an exhausted state and its associated gene expression profile in the BTLA C cells that may have been detectable if the TIL were analyzed directly ex vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 It should be noted that our gene expression profiling was performed after a period of expansion of isolated TIL with IL-2 in order to generate enough cells for analysis. This may have reversed an exhausted state and its associated gene expression profile in the BTLA C cells that may have been detectable if the TIL were analyzed directly ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…C PD-1 ¡ CD45RA C T EMRA cells in lymphocytes from normal donors, 17,18 and senescent human CD8 C CD28 ¡ T cells. 19,20 We confirmed the preferential protein expression of some KIR receptors in the CD8 C BTLA ¡ subset by flow cytometry (Fig.…”
Section: Differential Gene Expression Profiles Between Cd8mentioning
confidence: 99%
“…S2e,f). While PD-1 is widely known for its function as an inhibitory mediator, it is also known to function as an acute activation marker present on effector/ effector memory cells [31,32]. Given that our previous studies involving immunotherapy focused primarily on secondary lymphoid organs, we reasoned that tissue-resident memory cells, such as those found in the lung, are generally of the effector memory phenotype and may up-regulate representative of at least five independent experiments.…”
Section: Cd44mentioning
confidence: 99%
“…However, recent studies have revealed that PD-1 is also transiently expressed on the surface of effector T cells during earlier stages of activation (2,3). PD-1 mediates its inhibitory effect by clustering with the T-cell receptor (TCR) in the immunologic synapse and, after contacting either of its two known ligands (PD-L1 or PD-L2), recruiting SHP-2 phosphatase to its intracellular immunoreceptor tyrosine-based switch motif (ITSM; ref.…”
Section: Introductionmentioning
confidence: 99%